Magnesium Sulfate Prevents Placental Ischemia-Induced Increases in Brain Water Content and Cerebrospinal Fluid Cytokines in Pregnant Rats - Zhang, Linda W.; Warrington, Junie P. (Frontiers in Neuroscience, 2016)
Magnesium sulfate (MgSO4) is the most widely used therapy in the clinic to prevent the progression of preeclampsia, a hypertensive disorder of pregnancy, to eclampsia. Eclampsia, manifested as unexplained seizures and/or coma during pregnancy or postpartum, accounts for 13% of maternal deaths worldwide. While MgSO4 continues to be used in the clinic, the mechanisms by which it exerts its protective actions are not well understood. In this study, we tested the hypothesis that MgSO4 protects against placental ischemia-induced increases in brain water content and cerebrospinal fluid cytokines. To test this hypothesis, MgSO4 was administered via mini-osmotic pump (60 mg/day, i.p.) to pregnant and placental ischemic rats, induced by mechanical reduction of uterine perfusion pressure, from gestational day 14-19. This treatment regimen of MgSO4 led to therapeutic level of 2.8±0.6 mmol/L Mg in plasma. MgSO4 had no effect on improving placental ischemia-induced changes in mean arterial pressure, number of live fetuses, or fetal and placental weight. Placental ischemia increased, while MgSO4 prevented the increase in water content in the anterior cerebrum. Cytokine and chemokine levels were measured in the cerebrospinal fluid using a multi-plex assay. Results demonstrate that cerebrospinal fluid, obtained via the cisterna magna, had reduced protein, albumin, interleukin (IL)-17A, IL-18, IL-2, eotaxin, fractalkine, interferon gamma, vascular endothelial growth factor (VEGF), and macrophage inflammatory protein (MIP)-2 following MgSO4 treatment. These data support the hypothesis that MgSO4 offers neuroprotection by preventing placental ischemia-induced cerebral edema and reducing levels of cytokines/chemokines in the cerebrospinal fluid.